Inconsistencies in the mean fields of temperature, geopotential height and winds over the Indian aerological network during July-August - ANANTHAKRISHNAN , R.; SOMAN, M. K. (MAUSAM, 1992)
The daily aerological data of 23 RS/R W stations for the p ak monsoon months of July and August 1978, 1979 and 1980 for 25 levels from the surface to the lower stratosphere have been analysed. The standard deviations of the daily values of temperature are found to be about 1 .5 to 2° C in th9 lower troposphere increasing to about twice this value at upper levels. The standard deviations of geopotential heights or isobaric levels range from 15to 30 gpm in the lower troposphere increasing to about 4 times this value at upper levels. The horizontal gradients in the mean fields of temperature and geopotential height between pairs of stations in the network show several inconsistencies which are illustrated with examples. The existence of such inconsistencies in the mean fields for several years has also been found from an examination of CLIMAT -TEMP data of the stations up to 1989. These findings impose limitations on the utilisation of the data in synoptic and climatological studies.